Odpowiedzi

2010-02-03T19:46:20+01:00
A) = (x-2)(x^2+1)
b) = (x+1)(2x^2+3)
c) = (x-2)(x^2-4) = (x-2)(x+2)(x-2)
d) = (x+3)(4x^2-1) = (x+3)(2x+pierwiastek z 1) (2x-pierwiastek z 1)
Najlepsza Odpowiedź!
2010-02-03T20:58:57+01:00
Zakończ rozkładanie wielomianu w na czynniki
a) w(x)= x³-2x²+x-2=x²(x-2)+(x-2)=(x-2)(x²+1)
b) w(x)=2x³+2x²+3x+3=2x²(x+1)+3(x+1)=(x+1)(2x²+3)
c) w(x)=x³-2x²-4x+8=x²(x-2)-4(x-2)=(x-2)(x²-4)=(x-2)(x-2)(x+2)=(x-2)²(x+2)
d) w(x)=4x³+12x²-x-3=4x²(x+3)-(x+3)=(x+3)(4x²-1)=(x+3)(2x-1)(2x+1)